Enhanced Quinolone Resistance and Differential Expression of Efflux Pump nor Genes in Staphylococcus aureus Grown in Platelet Concentrates - Carina Paredes; Que Chi Truong-Bolduc; Yin Wang; David C. Hooper; Sandra Ramirez-Arcos (Antibiotics, 2025)
Background/Objective: Platelet concentrates (PCs) are used in transfusion medicine to treat bleeding disorders. Staphylococcus aureus, a predominant PC contaminant, has been implicated in several adverse transfusion reactions. The aim of this study was to investigate the impact of PC storage on S. aureus resistance to quinolones, which are commonly used to treat S. aureus infections. Methods/Results: Four transfusion-relevant S. aureus strains (TRSs) were subjected to comparative transcriptome analyses when grown in PCs vs. trypticase soy broth (TSB). Results of these analyses revealed differentially expressed genes involved in antibiotic resistance. Of interest, the norB gene (encodes for the NorB efflux pump, which is implicated in quinolone resistance and is negatively regulated by MgrA) was upregulated (1.2–4.7-fold increase) in all PC-grown TRS compared to TSB cultures. Minimal Bactericidal Concentration (MBC) of ciprofloxacin and norfloxacin in PC-grown TRS compared to TSB showed increased resistance to both quinolones in PC cultures. Complementary studies with non-transfusion-relevant strains S. aureus RN6390 and its norB and mgrA deletion mutants were conducted. MBC of ciprofloxacin and norfloxacin and RT-qPCR assays of these strains showed that not only norB, but also norA and norC may be involved in enhanced quinolone resistance in PC-grown S. aureus. The role of norB in S. aureus virulence was also tested using the silkworm Bombyx mori animal model; lethal dose 50 (LD50) assays revealed slightly higher virulence in larvae infected with the wild-type strain compared to the norB mutant. Conclusions: The PC storage environment enhances quinolone resistance in S. aureus and induces differential expression of efflux pump nor genes. Furthermore, our preliminary data of the involvement of NorB in virulence of S. aureus using a silkworm model merit further investigation with other systems such as a mammal animal model. Our results provide mechanistic insights to aid clinicians in the selection of antimicrobial treatment of patients receiving transfusions of S. aureus-contaminated PCs.